1999
DOI: 10.1017/s1355838299990829
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant mRNAs with extended 3′ UTRs are substrates for rapid degradation by mRNA surveillance

Abstract: The mRNA surveillance system is known to rapidly degrade aberrant mRNAs that contain premature termination codons in a process referred to as nonsense-mediated decay. A second class of aberrant mRNAs are those wherein the 39 UTR is abnormally extended due to a mutation in the polyadenylation site. We provide several observations that these abnormally 39-extended mRNAs are degraded by the same machinery that degrades mRNAs with premature nonsense codons. First, the decay of the 39-extended mRNAs is dependent on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
160
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 211 publications
(169 citation statements)
references
References 34 publications
8
160
1
Order By: Relevance
“…Consistent with this model, the majority of yeast 39 UTRs are homogeneous in length and aberrant transcripts with exceptionally long 39 UTRs are substrates for NMD (Muhlrad and Parker 1999). In contrast, the requirement for a splicing-dependent signal seems to be a particular feature of mammalian NMD, and it is well established that EJCs play a pivotal role in the mechanism of PTC definition (Behm-Ansmant et al 2007).…”
Section: Discussionmentioning
confidence: 74%
“…Consistent with this model, the majority of yeast 39 UTRs are homogeneous in length and aberrant transcripts with exceptionally long 39 UTRs are substrates for NMD (Muhlrad and Parker 1999). In contrast, the requirement for a splicing-dependent signal seems to be a particular feature of mammalian NMD, and it is well established that EJCs play a pivotal role in the mechanism of PTC definition (Behm-Ansmant et al 2007).…”
Section: Discussionmentioning
confidence: 74%
“…The extended 3' UTR length by the premature stop codon is longer, and the mRNA is more degraded [19].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies perspicuously indicated that abnormal 3 UTR modified by deletion or mutation may induce a rapid degradation of the metallothionein mRNA (Muhlrad and Parker, 1999;Levadoux-Martin et al, 2001). Some previous studies demonstrated that a tandem repeat of a CACC could be essential for the transcript localization Nury et al, 2005).…”
Section: The Structural Analysis Of Metallothioneinmentioning
confidence: 99%